AURAT MARCH: CLASH OF SOCIAL AND RELIGIOUS PERSPECTIVES ON WOMEN’S ISSUES - Mr. Usman Haidar; Dr. Saeed Ahmad (Journal of Religion and Society, 2024)
The Aurat March, an annual event in Pakistan, has become a significant platform for advocating women’s rights, gender equality, and social justice. This movement, which began in 2018, highlights key issues such as gender-based violence, workplace harassment, and bodily autonomy. However, it also faces significant opposition from conservative and religious factions, who argue that its slogans and demands contradict Islamic teachings and traditional family values. This article explores the complex intersection between social advocacy for women's rights and the resistance rooted in religious and cultural values in Pakistan. The study examines both supportive and critical perspectives on the Aurat March, shedding light on the points of convergence, such as shared concerns about women’s safety and education, as well as fundamental differences in views on autonomy and morality. The role of media in shaping public opinion, either exacerbating or bridging this divide, is also explored. Furthermore, the article discusses the impact of this conflict on public opinion, legislative reforms, and the future of activism in Pakistan. It concludes with recommendations for bridging the divide between social and religious perspectives, including fostering dialogue, promoting women’s rights within a culturally sensitive framework, and leveraging education to reduce polarization. This paper aims to contribute to a deeper understanding of the challenges and opportunities in advancing women’s rights in Pakistan while navigating its socio-religious complexities. Keywords: Aurat March, women’s rights, gender equality, Pakistan, social advocacy, religious perspectives, autonomy, cultural values, media influence, polarization, activism, legislative reforms.